Web visibility in search engines: algorithmic factors of on-page SEO (FAOPs) as a journalistic technique and practice - Pedrosa, Leyberson [UNESP] (2021)
This study identifies Search Engine Optimization (SEO) factors to improve the visibility of journalistic information in search engines. This work claims that certain specific on-page SEO factors have features that are notably algorithmic and can be used during the process of production, edition, revision and distribution of journalistic content. Through benchmarks and conceptual maps, we identify seven on-page SEO factors, denominated On-Page Algorithmic Factors (OPAFs), that lead to input data affecting the results of algorithmic formulas. The use of these factors is compared to existing journalistic practices, such as writing a lead. Thus, this work proposes a preliminary set of questions based on the OPAFs and whose answers work as a lead for search engines, mainly Google, without compromising the ethical principles of journalism.